DOESPUBLIC CAPITAL EXPENDITURESAND INFRASTRUCTURE INFLUENCES THEGROSS DOMESTIC REGIONAL PRODUCT OFINDONESIANMANUFACTURING INDUSTRIES ? (ASTUDY ON INDONESIAN PROVINCES) - SE, Christian Siauwijaya (Jurnal Ilmiah Mahasiswa FEB, 2019)
This research empirically examines the relationship between public capital expenditures and road and electricity infrastructure on the output of manufacturing industry during 2013-2017 using Cobb-Douglas production function as its theoretical framework. The dependent variable used in this study adopts the panel data of 34 Indonesian provinces on real Gross Domestic Regional Product based on production. The independent variables used in this study are public capital expenditure, length of road, and electricity sales to represent infrastructure. The number of employed labor force in 34 Indonesian provinces is used as the control variable. This study finds that public capital expenditure, length of road, electricity sales, and employment have a positive and significant effect on the real Gross Domestic Regional Product of manufacturing industry.KEYWORDS: public capital expenditure, manufacturing industry, infrastructure development, CobbDouglas production function, regional budget allocation